Injury activated alveolar progenitors (IAAPs): the underdog of lung repair - Chong, Lei; Ahmadvand, Negah; Noori, Afshin; Lv, Yuqing; Chen, Chengshui; Bellusci, Saverio; Zhang, Jin-San; Justus Liebig University Giessen (My University, 2023)
Alveolar epithelial type II cells (AT2s) together with AT1s constitute the epithelial lining of lung alveoli. In contrast to the large flat AT1s, AT2s are cuboidal and smaller. In addition to surfactant production, AT2s also serve as prime alveolar progenitors in homeostasis and play an important role during regeneration/repair. Based on different lineage tracing strategies in mice and single-cell transcriptomic analysis, recent reports highlight the heterogeneous nature of AT2s. These studies present compelling evidence for the presence of stable or transitory AT2 subpopulations with distinct marker expression, signaling pathway activation and functional properties. Despite demonstrated progenitor potentials of AT2s in maintaining homeostasis, through self-renewal and differentiation to AT1s, the exact identity, full progenitor potential and regulation of these progenitor cells, especially in the context of human diseases remain unclear. We recently identified a novel subset of AT2 progenitors named “Injury-Activated Alveolar Progenitors” (IAAPs), which express low levels of Sftpc, Sftpb, Sftpa1, Fgfr2b and Etv5, but are highly enriched for the expression of the surface receptor programmed cell death-ligand 1 (Pd-l1). IAAPs are quiescent during lung homeostasis but activated upon injury with the potential to proliferate and differentiate into AT2s. Significantly, a similar population of PD-L1 positive cells expressing intermediate levels of SFTPC are found to be expanded in human IPF lungs. We summarize here the current understanding of this newly discovered AT2 progenitor subpopulation and also try to reconcile the relationship between different AT2 stem cell subpopulations regarding their progenitor potential, regulation, and relevance to disease pathogenesis and therapeutic interventions.
Keywords: ddc:610